The opinion system : impasses of the public sphere from Hobbes to Habermas - Wetters, Kirk (UPCC book collections on Project MUSE., 2008)
This title revises the concept of the public sphere by examining opinion as a foundational concept of modernity. It focuses on interpretive shifts begun in the Enlightenment and cemented by the French Revolution to restore the concept of 'opinion' to a central role in our understanding of the political public sphere.